2015
DOI: 10.1002/adfm.201503366
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Supramolecular Assembly to Fabricate 3D Ordered Structures: Towards Potential Tissue Scaffolds with Targeted Modification

Abstract: 3D ordered structures beyond microscale with targeted modification are catching increasing attention due to its application as tissue scaffolds. Especially scaffolds with necessary growth factors at designated locations are meaningful for induced cell differentiation and tissue formation. However, few fabrication methods can address the challenge of introducing bioactive species to the interior targeted places during the preparation process. Herein, for the first time macroscopic supramolecular assembly is app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 35 publications
0
51
0
1
Order By: Relevance
“…Ab ioactive scaffold for tissue engineering was introduced by Shi and co-workers. [153] Magnetically modified poly(dimethylsiloxane) bars were coated with b-CD-functionalized PA Ao ra zobenzene-functionalized PA At hrough layer-by-layer assembly with poly-(diallyldimethylammonium chloride). Finally,s tacks of the bars were formed through the influence of the magnetic field.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Ab ioactive scaffold for tissue engineering was introduced by Shi and co-workers. [153] Magnetically modified poly(dimethylsiloxane) bars were coated with b-CD-functionalized PA Ao ra zobenzene-functionalized PA At hrough layer-by-layer assembly with poly-(diallyldimethylammonium chloride). Finally,s tacks of the bars were formed through the influence of the magnetic field.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Herein we design three model systems with varied elastic modulus and correlated the MSA probability with the elasticity.Based on the effects of substrate deformability on multivalency,w eh ave proposed an elastic-modulus-dependent rule that building blocks belowacritical modulus of 2.5 MPac an achieve MSA for the used host/guest system. However,issues regarding whether the elastic modulus determines MSA or acritical boundary exists between assembly and nonassembly events are yet to be understood, which can probably provide auniversal design rule of MSA systems and establish afundamental basis for further applications of MSA in tissue scaffold fabrication, [10] self-healing materials, [11][12][13] underwater adhesion. [1][2][3][4] Originating from molecular assembly,the essence of MSA is non-covalent supramolecular interactions,but the difficulty of the assembly dramatically increases because the numerous interactive groups on two macroscopic surfaces must bind effectively to obtain ah igh association strength for the formation of assemblies.T herefore,e nhancing the recognition probability of supramolecular groups on the surface is key to improving the binding strength for MSA.…”
mentioning
confidence: 99%
“…[1][2][3][4] Originating from molecular assembly,the essence of MSA is non-covalent supramolecular interactions,but the difficulty of the assembly dramatically increases because the numerous interactive groups on two macroscopic surfaces must bind effectively to obtain ah igh association strength for the formation of assemblies.T herefore,e nhancing the recognition probability of supramolecular groups on the surface is key to improving the binding strength for MSA. However,issues regarding whether the elastic modulus determines MSA or acritical boundary exists between assembly and nonassembly events are yet to be understood, which can probably provide auniversal design rule of MSA systems and establish afundamental basis for further applications of MSA in tissue scaffold fabrication, [10] self-healing materials, [11][12][13] underwater adhesion. [3] Currently,m ost reports on MSA attained the aforementioned multivalent effects by either using highly flowable hydrogel systems [2,[5][6][7][8] or applying af lexible spacing coating to rigid materials, [3,9] such as, polydimethylsiloxane (PDMS), polymethyl methacrylate; both strategies reveal the intrinsic material property of low elastic modulus providing ah igh degree of freedom of the interactive moieties,u nderlying the success of MSA.…”
mentioning
confidence: 99%
“…For example, Huang et al [201] reported the method to fabricate hierarchical one-dimensional (1D) hydrogels architectures including nanotubes, coiled-coil ropelike structures, nanohelices, and nanoribbons via lanthanum-cholate supramolecular self-assembly, mediated by temperature. Besides, hydrogel patterns at micron scale or macro scale can also be obtained via supramolecular self-assembly [202][203][204]. These structured supramolecular hydrogels were anticipated to generate versatile applications in cell culture, tissue engineering, biomedical science and biosensor.…”
Section: Supramolecular Self-sssemblymentioning
confidence: 99%